In-group bias in the classroom: The role of co-ethnic and other-ethnic peers and multiculturalism - Thijs, Jochem; Verkuyten, Maykel (Anales de Psicología / Annals of Psychology, 2011)
This study among 322 native Dutch and 193 Turkish-Dutch early adolescents examined ethnic in-group bias in relation to two different aspects of the classroom context: the (aggregated) actual group evaluations of co-ethnic and other-ethnic classmates, and the multicultural classroom climate. Multilevel analyses showed that the in-group evaluation of co-ethnic peers was positively related to in-group bias, and that the out-group evaluation of co-ethnic peers had a negative effect. This latter effect was mediated by the children‟s own out-group attitude. The inand out-group evaluations of other-ethnic peers had no unique effects on in-group bias. Multicultural classroom climate had a negative effect on the in-group bias of native Dutch children but not of Turkish-Dutch children. Results show that in-group bias is uniquely affected by in-group peers and by the normative school context.